Generation of the UAE’s first Emirati induced pluripotent stem cell line KUSTi001-A from peripheral blood derived CD34+ hematopoietic cells - Sarah Kassem Azzam; Habiba Alsafar; Abdulrahim A. Sajini (Stem Cell Research, 2022)
Here we report the generation of the first Emirati iPSC line in the United Arab Emirates and name it KUSTi001-A. CD34+ hematopoietic cells purified from peripheral blood of a 27-year-old healthy female donor were reprogrammed using Sendai vectors. Twenty days post-reprogramming colonies were manually picked, and expanded clones were verified for transgene clearance by RT-PCR. Pluripotency was validated by pluripotency genes and differentiation into all three germ layers. Finally, chromosome stability was confirmed by testing 8 common abnormality loci. KUSTi001-A, alternatively called UAE001, is an Emirati hiPSC line that holds great potential for UAE specific regenerative medicine, disease modelling and drug screening.